2003
DOI: 10.1016/s0042-6822(03)00390-8
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis identifies differentiation-associated genes regulated by human papillomavirus type 16 E6

Abstract: In this study, we used oligonucleotide microarray analysis to determine which cellular genes are regulated by the human papillomavirus type 16 (HPV-16) E6 oncoprotein. We found that E6 causes the downregulation of a large number of cellular genes involved in keratinocyte differentiation, including genes such as small proline-rich proteins, transglutaminase, involucrin, elafin, and cytokeratins, which are normally involved in the production of the cornified cell envelope. In contrast, E6 upregulates several gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
78
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 32 publications
8
78
1
Order By: Relevance
“…Further studies will be necessary to elucidate the role of this mutated E6 protein of HPV83m in the immortalization process, which allows for the development of a cancer. Using microarray analysis, Duffy et al (2003) identified the host genes upregulated by expression of E6 of HPV16 and compared this expression profile with the profiles of cells that express variants of E6 of HPV16. A host transcription profile associated with an increased risk for malignant progression of HPV-associated lesions could represent a novel diagnostic tool for early detection of the evolution of potential malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies will be necessary to elucidate the role of this mutated E6 protein of HPV83m in the immortalization process, which allows for the development of a cancer. Using microarray analysis, Duffy et al (2003) identified the host genes upregulated by expression of E6 of HPV16 and compared this expression profile with the profiles of cells that express variants of E6 of HPV16. A host transcription profile associated with an increased risk for malignant progression of HPV-associated lesions could represent a novel diagnostic tool for early detection of the evolution of potential malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the activation of c-IAP2 transcription appeared to be associated with the transformation functions of highrisk E6 and E7 since low-risk HPV6 E6/E7 did not activate the c-IAP2 promoter. Also, HPV16 E6 mutants D118-122 (Foster et al, 1994), which is defective in telomerase activation (Duffy et al, 2003), failed to activate c-IAP2 expression. It has been shown that telomerase gene promoter contains two putative NF-kBbinding motifs (Yin et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…To further characterize the E6-mediated c-IAP2 upregulation, we examined the effect of two HPV16 E6 mutants 8S9A10T and D118-122, which are defective in the induction of p53 degradation and telomerase activation (Foster et al, 1994;Duffy et al, 2003). Both E6 mutants were not able to activate the c-IAP2 promoter (Figure 2b).…”
Section: Transcriptional Activation Of the C-iap2 Promoter By E6 And mentioning
confidence: 99%
“…AP-1 plays a major role in regulating the transcriptional expression of MMP genes (such as MMP-1, MMP-3, MMP-7, MMP-9 and MMP-10), the promoter regions of which contain AP-1 DNA elements (Auble et al, 1992;Benbow & Brinckerhoff, 1997;Loesch et al, 2010;Sato et al, 1993; Westermarck & KĂ€hĂ€ri, 1999;Yamamoto et al, 1995). These MMP genes can be stimulated by extracellular stimuli such as growth factors, cytokines and viral proteins (AkgĂŒl et al, 2005;Behren et al, 2005;Duffy et al, 2003; KĂ€hĂ€ri & Saarialho-Kere, 1997;Shapiro, 1998).A single AP-1 DNA motif (59-TGAGTCA-39), which putatively binds the AP-1 transcription factors, was identified at nt 277 in the promoter region of the equine MMP-1 gene ( Supplementary Fig. S1).…”
mentioning
confidence: 99%